Because We Can Doesn't Mean We Should and if We Do: Urban Communities, Social and Economic Justice, and Local Economic-Development-Driven Eminent Domain Practices. (August 2015) - Harris, Kirk E.
One powerful expression of the neoliberal orthodoxy within economic development practice in the United States has been local governments' use of economic-development-driven eminent domain. However, the presumed benefits but not the actual harm of the eminent domain actions typically eludes the working-class and low-income segments of the community that often shoulder the greatest consequences of the action. Municipal governments must be much more exacting, deliberative, and strategic in ensuring there is an obvious and direct connection between the potential economic development opportunities leveraged by eminent domain practices and the benefits, opportunities, and resources that the community derives from those transactions of local government. Thoughtfully and strategically designed and executed Community Benefit Agreements have tremendous potential to afford working-class and low-income residents, as well other city residents, a chance for more equitable and democratic results than they frequently experience under existing economic-development-driven eminent domain practice.